Healing through the lens of immunothrombosis: Biology-inspired, evolution-tailored, and human-engineered biomimetic therapies. (December 2021) - Padilla, Sabino; Nurden, Alan T.; Prado, Roberto; Nurden, Paquita; Anitua, Eduardo
Abstract: Evolution, from invertebrates to mammals, has yielded and shaped immunoclotting as a defense and repair response against trauma and infection. This mosaic of immediate and local wound-sealing and pathogen-killing mechanisms results in survival, restoration of homeostasis, and tissue repair. In mammals, immunoclotting has been complemented with the neuroendocrine system, platelets, and contact system among other embellishments, adding layers of complexity through interconnecting blood-born proteolytic cascades, blood cells, and the neuroendocrine system. In doing so, immunothrombosis endows humans with survival advantages, but entails vulnerabilities in the current unprecedented and increasingly challenging environment. Immunothrombosis and tissue repair appear to go hand in hand with common mechanisms mediating both processes, a fact that is underlined by recent advances that are deciphering the mechanisms of the repair process and of the biochemical pathways that underpins coagulation, hemostasis and thrombosis. This review is intended to frame both the universal aspects of tissue repair and the therapeutic use of autologous fibrin matrix as a biology-as-a-drug approach in the context of the evolutionary changes in coagulation and hemostasis. In addition, we will try to shed some light on the molecular mechanisms underlying the use of the autologous fibrin matrix as a biology-inspired, evolution-tailored, and human-engineered biomimetic therapy.